DESKRIPSI KESALAHAN MAHASISWA DALAM MENYELESAIKAN SOAL NUMERASI DITINJAU DARI ASPEK SELF-EFFICACY - Ariany, Rizta; Kusnadi, Dedi; Nanna, A. Wilda Indra (Universitas Borneo Tarakan, 2026)
Students' errors in solving numeracy problems are closely related to their self-efficacy levels, which influence their confidence in understanding and solving problems. This study aims to describe students' errors in solving numeracy problems from a self-efficacy perspective. The study used a descriptive qualitative approach with students categorized based on low, medium, and high levels of self-efficacy. Data were collected through questionnaires, numeracy tests, and interviews, and analyzed using Newman's stages. The results showed that students with low self-efficacy made errors in the reading stage. Students with medium and high self-efficacy showed errors in understanding the problems, which resulted in errors in Transformation, Processing skills, and Encoding. This study emphasizes the importance of recognizing errors in solving numeracy problems to improve students' numeracy skills.